2020
DOI: 10.1016/j.enpol.2020.111295
|View full text |Cite
|
Sign up to set email alerts
|

Renewable energy consumption and economic growth nexus: Evidence from a threshold model

Abstract: The existing literature on renewable energy consumption and economic growth nexus produces mixed results as the effect of renewable energy consumption on economic growth can be either positive, negative or not significant. This paper examines the causal link between renewable energy use and economic growth by employing a threshold model using a 103-country sample in the 1995 to 2015 period. We find that the relationship between renewable energy consumption and economic growth depends on the amount of renewable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
142
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(153 citation statements)
references
References 64 publications
(122 reference statements)
9
142
0
2
Order By: Relevance
“…The existence of differences among energy transition patterns of countries is in line with Chen et al (2019) and Chen et al (2020) who found out the dissimilar relationship between carbon dioxide emissions and renewable energy consumption across different regions.…”
Section: Concluding Remarks and Policy Recommendationssupporting
confidence: 70%
“…The existence of differences among energy transition patterns of countries is in line with Chen et al (2019) and Chen et al (2020) who found out the dissimilar relationship between carbon dioxide emissions and renewable energy consumption across different regions.…”
Section: Concluding Remarks and Policy Recommendationssupporting
confidence: 70%
“…The study results of Chen et al [15] show that for developing countries to achieve positive economic growth through investment in renewable energy, they need to overcome a certain threshold of renewable energy consumption.…”
Section: Economic Growthmentioning
confidence: 99%
“…Their findings revealed that renewable energy production is associated with a positive and statistically significant impact on economic growth in both developed and developing countries for the period 1995 to 2016.Their results also showed that the impact of renewable energy production on economic growth is higher in developing economies, as compared to developed economies. Chen, Pinar, and Stengos (2020) examined the causal relationship between renewable energy use and economic growth by employing a threshold model using a 103-country sample from 1995 to 2015 period and found that the effect of renewable energy consumption on economic growth is positive and significant if and only if developing countries surpass a certain threshold of renewable energy consumption. Their results further revealed that if developing countries use renewable energy below a given threshold level, the effect of renewable energy consumption on economic growth is negative.…”
Section: Literature Reviewmentioning
confidence: 99%